Sorteo del Proyecto de Vinculación de Enfermería - Llivi Ruilova, Danny Vicente (2023)
With the presence of Mgtr. Silvana López Paredes, dean of the Faculty of Health and Human Sciences; Mgtr. María Olalla, head of the Nursing career and Eng. Manuel Yanez, coordinator of the Peasant Social Security; The drawing was held for the Linkage Project called “Comprehensive cultural care to improve the healthy lifestyle of families affiliated with the Peasant Social Security, third phase, based on the current agreement with the State University of Bolívar.